Interventional radiology - Chung Han, M.D., Man; Jae Hyung Park, M.D (Seoul, Korea : ILCHOKAK, 1999)
Interventional radiology is at this time probably the most successful and impressive field of radiology, rapidly advancing abd taking advantage of all the techniques of imaging.
Part 1 VASCULAR INTERVENTION I. Embolotherapy 1. Embolization: principles, techniques and material 2. Bronchial arterial embolization 3. Renal arterial emnolization 4. Embolization in abdominal visceral organs 5. Embolotherapy of varicocele 6. Radiological intervention for hemangiomas and vascular malformations II. Transcatheter management of hepatic tumors 7. Hepatic artery chemoembolization and infusion chemotherapy 8. Lipiodol Chemoembolization: Principles adn techniques 9. Segmental and subsegmental lipiodol chemoembolization y otros más III. Arterial recanalization 16. Principles,periprocedural assessment and materials for percutaneous transluminal angiosplasty and stenting y otros más IV. Aortic intervention 22. Aortoiliac occlusive diseases y otros más V.Venous interventions VI. Neurovascular intervention VII. Miscellaneous vascular intervention Part 2. NONVASCULAR INTERVENTION VIII. Hepatobiliary intervention IX. Urogenital intervention X. Thoracic Intervention XI. Gastrointestinal and abdominal intervention XII. Miscellaneous nonvascular intervention
Incluye índice de contenido, índice de materia
Incluye Bibliografía
Keywords: INSUFICIENCIA VENOSA; VENAS -- TRANSPLANTES